Improved metastability and performance of amorphous silicon solar cells. Issue 1666 (3rd November 2014) - Matsui, Takuya; Bidiville, Adrien; Sai, Hitoshi; Suezaki, Takashi; Matsumoto, Mitsuhiro; Saito, Kimihiko; Yoshida, Isao; Kondo, Michio
ABSTRACT: We show that high-efficiency and low-degradation hydrogenated amorphous silicon (a-Si:H) p-i-n solar cells can be obtained by depositing absorber layers in a triode-type plasma-enhanced chemical vapor deposition (PECVD) process. Although the deposition rate is relatively low (0.01-0.03 nm/s) compared to the conventional diode-type PECVD process (∼0.2 nm/s), the light-induced degradation in conversion efficiency of single-junction solar cell is substantially reduced (Δη/ηini ∼10%) due to the suppression of light-induced metastable defects in the a-Si:H absorber layer. So far, we have attained an independently-confirmed stabilized efficiency of 10.11% for a 220-nm-thick a-Si:H solar cell which was light soaked under 1 sun illumination for 1000 hours at cell temperature of 50°C. We further demonstrate that stabilized efficiencies as high as 10% can be maintained even when the solar cell is thickened to >300 nm.